Security and Cooperation in South Asia - Edited by Gajurel, Deepak (Kathmandu, Nepal Spotlight Newsmagazine, 2003)
Contributed papers presented at Seminar on Security and Cooperation in South Asia, August 6-7, 2003, Kathmandu, Nepal.
Include Colour Illustration
Keywords: National security--International cooperation -- South Asia